Ceramic-based gradient composite thermal insulation expansion joint device for high temperature piping

CN122813083APending Publication Date: 2026-09-25SHENYANG HONGQI THERMAL EQUIP MFG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610879622.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-17
Publication Date
2026-09-25

AI Technical Summary

Technical Problem

在高温区域极易发生焚化、脱落,导致工艺管道外壁温度过高、漏风严重,且使用寿命较短,休风率高,严重制约了高温管道系统的稳定作业

Benefits of technology

[0012]与现有技术相比,本发明的内衬由三层组成,红外辐射层的结构致密,与基体结合力强,耐机械冲击和热冲击。涂层的黑度可保证其在波长2.5~15μm的光谱区间,发射率都在0.9以上,其应用可进一步降低风管中热风能量的损耗。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122813083A_ABST
    Figure CN122813083A_ABST
Patent Text Reader

Abstract

A ceramic-based gradient composite heat insulation expansion joint device for high-temperature pipelines comprises a body and an inner lining arranged in the pipeline body, the inner lining comprising an infrared radiation coating, a low-thermal-conductivity heat insulation layer and an erosion-resistant heat insulation layer, the infrared radiation coating, the low-thermal-conductivity heat insulation layer and the erosion-resistant heat insulation layer being arranged in sequence from inside to outside, the low-thermal-conductivity heat insulation layer being made by pouring, curing and flame baking of raw materials comprising the following components by mass percentage: 0.5-1.5% of polypropylene fibers, 35-40% of alumina hollow spheres, 15-20% of lightweight mullite, 8-12% of silicon powder, 5-8% of alumina powder, 3-5% of kyanite powder, 8-12% of ceramic fibers and 8-12% of cement. The device can greatly improve the fire resistance, heat insulation performance and service life of the expansion joint. The patent can be produced in batches, and the on-site cooling rate is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-temperature industrial process piping technology, and in particular to a ceramic-based gradient composite thermal insulation expansion joint device for high-temperature pipelines. Background Technology

[0002] In high-temperature industrial processes, numerous pipelines are required to transport high-temperature heat source media to the terminals, and their operational stability directly affects the continuity and energy efficiency of the production system. Expansion joints, as core components connecting multi-dimensional pipeline systems, not only bear the functions of thermal compensation and connection sealing for complex piping systems, but are also a crucial link in ensuring low-loss heat energy transmission. Currently, the industry commonly uses internal insulation linings to achieve energy saving and protection; however, existing internal insulation lining materials have significant shortcomings in terms of physical and mechanical properties and manufacturing processes. Especially in smelting processes, pipelines need to deliver hot air heated to 1250-1350℃ by the hot blast stove into the main blast furnace unit. In high-temperature areas, combustion and detachment are highly likely, leading to excessively high outer wall temperatures, severe air leakage, short service life, and high downtime rates, seriously restricting the stable operation of high-temperature pipeline systems.

[0003] Therefore, refractory materials in high-temperature zones require strong resistance to chemical erosion and airflow scouring. This also places new technical demands on the performance of new expansion joints. Summary of the Invention

[0004] This invention provides a ceramic-based gradient composite thermal insulation expansion joint device for high-temperature pipelines, which can greatly improve the fire resistance, thermal insulation performance and service life of the expansion joint.

[0005] The present invention solves the above-mentioned technical problems through the following technical solutions: A ceramic-based gradient composite thermal insulation expansion joint device for high-temperature pipelines includes a body and an inner liner. The inner liner is disposed within the pipeline body and comprises an infrared radiation coating, a low thermal conductivity insulation layer, and a corrosion-resistant insulation layer, arranged sequentially from the inside to the outside. The low thermal conductivity insulation layer is made from raw materials containing the following components by mass percentage through casting, curing, and flame baking: The proportion of polypropylene fiber is 0.5%-1.5%. Hollow alumina spheres account for 35%-40%. The proportion of lightweight mullite is 15%-20%. The proportion of silicon micropowder is 8%-12%. The proportion of alumina micro powder is 5%-8%. The proportion of kyanite powder is 3%-5%. The proportion of ceramic fiber is 8%-12%. Cement accounts for 8%-12%.

[0006] The aforementioned ceramic-based gradient composite thermal insulation expansion joint device for high-temperature pipelines comprises a corrosion-resistant thermal insulation layer formed by ball milling, spraying with deionized water, and fast-sweeping drying and curing with an oxy-acetylene flame, using raw materials containing the following components in the specified mass percentages: The proportion of zirconium silicate micro powder is 70%-75%. Aluminum dihydrogen phosphate accounts for 20%-25%. The proportion of alumina fiber is 3%-5%. Zirconia fiber accounts for 2%-4%.

[0007] The aforementioned ceramic-based gradient composite thermal insulation expansion joint device for high-temperature pipelines comprises an infrared radiation coating formed by ball milling, spraying, and curing a coating containing the following components in the specified mass percentages: Aluminum dihydrogen phosphate accounts for 25%-30%. The proportion of manganese dioxide is 25%-30%. The content of ferric oxide is 20%-25%. The proportion of copper oxide is 5%-8%. Chromium trioxide accounts for 4%-6% of the total content. Nickel oxide accounts for 3%-5%, The titanium dioxide content is 3%-5%. Cerium oxide accounts for 2%-4%.

[0008] The above-mentioned ceramic-based gradient composite thermal insulation expansion joint device for high-temperature pipelines includes an end pipe, a corrugated pipe, and a connector. There are two end pipes, and the corrugated pipe is located between the two end pipes. The two ends of the corrugated pipe are welded to the end pipes. The connector crosses the corrugated pipe and connects to the end pipe. The inner lining is located inside the pipe channel.

[0009] The aforementioned ceramic-based expansion joint for high-temperature pipelines also includes an outer liner, which is disposed outside the end pipe and the bellows. The outer liner and the inner liner are arranged symmetrically in terms of their layer structure.

[0010] The ceramic-based expansion joint for high-temperature pipelines mentioned above includes several sets of components. Each set of components includes a connecting screw, a nut, and a connecting plate. There are two connecting plates, which are respectively fixed to the end pipe. One end of the connecting plate is connected to the end pipe, and the other end is provided with a through hole. The connecting screw passes through the through hole and is fixed by the nut.

[0011] The aforementioned ceramic-based expansion joint for high-temperature pipelines includes an outer protective cover and anchors. These anchors are fixed to the side wall of the end pipe and are Y-shaped, extending into the low thermal conductivity insulation layer. The infrared radiation coating 3 has a thickness of 0.8-1.5 mm; the low thermal conductivity insulation layer 4 has a thickness of 10-30 mm; and the corrosion-resistant insulation layer 5 has a thickness of 1-2 mm.

[0012] Compared with existing technologies, the lining of this invention consists of three layers. The infrared radiation layer has a dense structure, strong adhesion to the substrate, and resistance to mechanical and thermal shock. The coating's emissivity is guaranteed to be above 0.9 in the spectral range of 2.5–15 μm, and its application can further reduce the loss of hot air energy in the duct.

[0013] In the low thermal conductivity insulation layer, polypropylene fibers undergo high-temperature ablation to form micropores, enhancing insulation performance. Kyanite powder transforms into mullite at high temperatures to compensate for volume shrinkage, while ceramic fibers enhance high-temperature toughness. Simultaneously, both alumina hollow spheres and mullite are low thermal conductivity ceramic materials with strong bonding to calcium aluminate cement. Therefore, through the formulation of these materials, a low thermal conductivity, crack-resistant duct lining can be obtained. The corrosion-resistant insulation layer provides effective thermal erosion protection for the intermediate low thermal conductivity insulation layer, significantly improving the overall service life of high-temperature pipeline insulation in industrial processes.

[0014] This patent allows for mass production, reducing the thermal conductivity of the hot surface to 6.9% at 1000℃, and preventing radial through-cracks within a 12-month service life. Furthermore, infrared radiation coatings are applied to the inner and outer surfaces of flexible pipe fittings in high-temperature pipelines for thermal protection, reducing the outer wall temperature of high-temperature flexible pipeline systems by 18%-40%, increasing effective lifespan by 1-1.5 times, and reducing on-site downtime rate by 12%. Attached Figure Description

[0015] Figure 1 This is a schematic diagram of the internal structure of the present invention; Figure 2 This is a schematic diagram of the inner lining structure of the present invention; Figure 3 This is a schematic diagram of the axial structure of the present invention; The markings in the attached diagram represent: 1. Pipe body, 2. Inner lining, 3. Infrared radiation coating, 4. Low thermal conductivity insulation layer, 5. Corrosion resistant insulation layer, 6. Outer lining, 7. Outer protective cover, 8. Corrugated pipe, 9. Connector, 10. Anchor, 11. End pipe, 91. Connecting screw, 92. Nut, 93. Connecting plate. Detailed Implementation

[0016] The specific embodiments of the present invention will be described in further detail below with reference to the accompanying drawings and examples. The following examples are used to illustrate the present invention.

[0017] like Figure 1-3 As shown, the present invention includes a tube body 1 and an inner liner 2. The inner liner 2 is disposed inside the tube body 1. The inner liner 2 includes an infrared radiation coating 3, a low thermal conductivity insulation layer 4, and a corrosion-resistant insulation layer 5. The infrared radiation coating 3, the low thermal conductivity insulation layer 4, and the corrosion-resistant insulation layer 5 are arranged sequentially from the inside to the outside. The thickness of the infrared radiation coating 3 is 0.8-1.5 mm; the thickness of the low thermal conductivity insulation layer 4 is 10-30 mm; and the thickness of the corrosion-resistant insulation layer 5 is 1-2 mm.

[0018] The components of the low thermal conductivity insulation layer 4 are: The proportion of polypropylene fiber is 0.5%-1.5%. Hollow alumina spheres account for 35%-40%. The proportion of lightweight mullite is 15%-20%. The proportion of silicon micropowder is 8%-12%. The proportion of alumina micro powder is 5%-8%. The proportion of kyanite powder is 3%-5%. The proportion of ceramic fiber is 8%-12%. Cement accounts for 8%-12%.

[0019] Alumina hollow spheres and lightweight mullite are used as the main raw materials to achieve low thermal conductivity and improved thermal stability. Polypropylene fiber is used as the filler to resist drying cracking, and ceramic fiber is used as the reinforcing phase to help resist cracking. Silica powder and alumina powder are used as fillers to promote sintering; kyanite powder is used as a high-temperature expansion compensator, and cement is used as a binder; the cement is preferably calcium aluminate cement; tap water is used as the dispersion medium, and a vibratory ceramic slurry is obtained by mixing. A stainless steel mandrel is fixed in the middle of the low thermal conductivity insulation layer 4, and then the ceramic slurry is poured into the gaps in the insulation layer. After the ceramic slurry has solidified, the mandrel is removed and baked in a flame oven until completely dry. Adding polypropylene fibers to the low thermal conductivity insulation layer 4 can significantly improve the crack resistance of the insulation layer during the cement curing process. At the same time, the polypropylene fibers are gradually burned off during the baking process, which creates tiny pores in the insulation layer and increases the thermal resistance of the insulation layer. The addition of inorganic fibers significantly improves the crack resistance of the low thermal conductivity insulation layer 4 at high temperatures, reduces heat transfer, and lowers the temperature of the outer wall.

[0020] The performance parameters of the low thermal conductivity insulation layer of this formulation are as follows: Bulk density: 1.15~1.25 g / cm3; Compressive strength (110℃×24h): 12.0~13.0MPa; Compressive strength (1250℃×3h): 13.5~14.5MPa; Thermal conductivity of the hot surface at 1000℃: 0.24~0.27 W / (m·K) Thermal shock resistance (1000℃ - air cooling): ≥20 times High-temperature linear shrinkage (1250℃×3h): ≤0.42% Performance: No radial through cracks were observed within a 12-month service life; excellent thermal insulation and crack resistance.

[0021] Furthermore, the components of the corrosion-resistant heat insulation layer 5 are as follows: The proportion of zirconium silicate micro powder is 70%-75%. Aluminum dihydrogen phosphate accounts for 20%-25%. The proportion of alumina fiber is 3%-5%. Zirconia fiber accounts for 2%-4%.

[0022] Zirconium silicate micropowder is the main raw material, which helps to improve erosion resistance and refractoriness. Aluminum dihydrogen phosphate is used as a binder, and alumina fiber and zirconium oxide fiber are used as reinforcing phases. These are added to a ball mill jar according to the above proportions and mixed into a ceramic coating by ball milling under air and room temperature. This coating is then sprayed onto the surface of the low thermal conductivity insulation layer 4 to form a coating layer. The coating surface is then rapidly dried and cured using an oxy-acetylene flame to obtain a dense, smooth, corrosion-resistant insulation layer 5. Aluminum dihydrogen phosphate and zirconium silicate form a dense, corrosion-resistant layer; the synergistic effect of alumina fiber and zirconium oxide fiber enhances thermal shock resistance and corrosion resistance, enabling it to withstand high-speed airflow erosion at 1250℃.

[0023] The corrosion-resistant thermal insulation layer 5 formed after curing can meet the following key technical indicators such as compressive strength, flexural strength, thermal conductivity, and thermal shock resistance at room temperature and high temperature: Bulk density ≤2.28 g / cm³; Compressive strength: ≥67.7MPa at 110℃×24h, ≥73.8MPa at 1250℃×3h; Flexural strength ≥ 9.9 MPa at 110℃×24h; ≥ 11.7 MPa at 1250℃×3h; Thermal conductivity of the hot surface at 1000℃ ≤ 0.79W / mk; Thermal shock resistance ≥10 times (1000℃ - air cooling).

[0024] Furthermore, the components of the infrared radiation coating 3 are: Aluminum dihydrogen phosphate accounts for 25%-30%. The proportion of manganese dioxide is 25%-30%. The content of ferric oxide is 20%-25%. The proportion of copper oxide is 5%-8%. Chromium trioxide accounts for 4%-6% of the total content. Nickel oxide accounts for 3%-5%, The titanium dioxide content is 3%-5%. Cerium oxide accounts for 2%-4%.

[0025] The main binder is aluminum dihydrogen phosphate, with manganese dioxide and ferric oxide preferred as base materials, and copper oxide, chromium oxide, nickel oxide, titanium dioxide and cerium oxide preferred as auxiliary materials. These are added to a ball mill jar in the following proportions and mixed by ball milling at room temperature. Then, deionized water is used to make a coating. The coating is then sprayed onto the inner or outer surface of the expansion joint insulation layer and cured by heating to obtain the infrared radiation coating 3.

[0026] This formulation ensures that the coating has an emissivity of ≥0.9 in the 2.5–15μm band, while aluminum dihydrogen phosphate provides strong adhesion. The base material and auxiliary materials work together to achieve high emissivity and thermal shock resistance.

[0027] The main body includes end tubes 11, corrugated pipes 8, and connectors 9. Two end tubes 11 are provided, and the corrugated pipe 8 is located between the two end tubes 11. Both ends of the corrugated pipe 8 are welded to the end tubes 11. The connector 9 crosses the corrugated pipe and connects to the end tube. An inner liner 2 is provided on the inner surface of the main body. An outer liner 6 is also provided, located on the outer surface of the main body. The outer liner 6 and the inner liner 2 are arranged symmetrically in layered structure. To ensure the stability of the overall structure, an outer protective cover 7 is also provided on the outer surface of the outer liner 6. Components are evenly distributed around the outer periphery of the end tubes. The connector 9 includes several sets of components. Each set of components includes a connecting screw 91, a nut 92, and a connecting plate 93. Two connecting plates 93 are provided, each fixed to the end tube. One end of the connecting plate 93 is connected to the end tube, and the other end has a through hole. The connecting screw passes through the through hole and is fixed by the nut 92. During installation, the end pipe is connected to the pipeline, and the connector sits above the corrugated pipe to ensure the stability of the pipeline. During use, the corrugated pipe compensates for the deformation of the pipeline.

[0028] To increase the structural stability of the inner and outer linings, anchors 10 are also provided. The anchors 10 are fixed to the side wall of the end tube 11. The anchors 10 are Y-shaped and extend into the low thermal conductivity insulation layer 4.

[0029] Liner 2, through a combination of materials with different physical and chemical properties, leverages the strengths of each material to create a synergistic effect. This invention boasts a lower thermal conductivity, higher strength, and resistance to cracking and erosion, reducing heat loss by approximately 15% or more. This significantly reduces the amount of material used and the unit heat loss for the same volume, achieving the ideal effect of refractory insulation and thus realizing energy conservation and consumption reduction. It also avoids the problem of duct deformation due to high temperatures. Compared with existing insulation materials, the service life of this invention can be increased by more than double, expected to reach 12-18 months. Furthermore, it can reduce the outer wall temperature of the blast furnace air supply system from the current 220-300℃ to below 180℃, and the on-site downtime rate from 2.03% to below 1.8%, reducing heat loss by more than 15%. Example 1

[0030] This invention includes a pipe body and an inner lining. The inner lining is disposed within the pipe body and comprises an infrared radiation coating, a low thermal conductivity insulation layer, and a corrosion-resistant insulation layer. These layers are arranged sequentially from the inside out. The infrared radiation coating 3 has a thickness of 1.2 mm; the low thermal conductivity insulation layer 4 has a thickness of 25 mm; and the corrosion-resistant insulation layer 5 has a thickness of 2 mm. The low thermal conductivity insulation layer has the following components: Polypropylene fiber accounts for 0.5%. Hollow alumina spheres account for 40%. Lightweight mullite accounts for 16%. The proportion of silicon micropowder is 8%. The alumina micro powder accounts for 6%. Kyanite powder accounts for 4%. Ceramic fiber accounts for 10%. Cement accounted for 11.5%.

[0031] The performance parameters are as follows: Bulk density: 1.15~1.2 g / cm3; Thermal conductivity of the hot surface at 1000℃: 0.26 W / (m·K) Compressive strength after drying at 110℃: 12.5MPa; Compressive strength after calcination at 1250℃: 14.2 MPa; Thermal shock resistance (1000℃ - air cooling): ≥22 cycles; High-temperature linear shrinkage rate: ≤0.4%, no radial through cracks within a 12-month service life.

[0032] Furthermore, the components of the corrosion-resistant heat insulation layer are: Zirconium silicate micro powder accounts for 70%. Aluminum dihydrogen phosphate accounts for 22%. Alumina fiber accounts for 4%. Zirconia fiber accounts for 4%.

[0033] The corrosion-resistant thermal insulation layer formed after curing can meet the following key technical requirements in terms of compressive strength, flexural strength, thermal conductivity, and thermal shock resistance at room temperature and high temperature: The bulk density is 2.27 g / cm³. 3 ; The compressive strength is 67.7 MPa at 110℃ for 24 hours and 73.8 MPa at 1250℃ for 3 hours. Flexural strength: 10 MPa at 110℃ for 24 hours; 12.5 MPa at 1250℃ for 3 hours. Thermal conductivity of the hot surface at 1000℃ = 0.79 W / (mk); Thermal shock resistance (1000℃ - air cooling) = 13 times.

[0034] Furthermore, the components of the infrared radiation coating are: Aluminum dihydrogen phosphate accounts for 25%. Manganese dioxide accounts for 25%. Ferric oxide accounts for 20%. Copper oxide accounts for 8%. Chromium trioxide accounts for 6% Nickel oxide accounts for 5%. Titanium dioxide accounts for 5%. Cerium oxide accounts for 4%.

[0035] This formulation ensures that the coating achieves an emissivity of 0.9 in the 2.5–15 μm band. Example 2

[0036] The difference between this embodiment and the above embodiment is that the thickness of the infrared radiation coating 3 is 1mm; the thickness of the low thermal conductivity insulation layer 4 is 15mm; and the thickness of the corrosion-resistant insulation layer 5 is 1.5mm.

[0037] The composition of the low thermal conductivity insulation layer is: Hollow alumina spheres account for 35%. Lightweight mullite accounts for 15%. Polypropylene fiber accounts for 1.5%. The proportion of silicon micropowder is 10%. The alumina micro powder accounts for 7%. Kyanite powder accounts for 5%. Ceramic fiber accounts for 11.5%. Cement accounts for 12%.

[0038] The performance parameters of the low thermal conductivity insulation layer of this component are as follows: Bulk density: 1.18~1.25 g / cm3; Thermal conductivity of the hot surface at 1000℃: 0.25 W / (m·K) Compressive strength after drying at 110℃: 12.0 MPa; Compressive strength after calcination at 1250℃: 13.5MPa; Thermal shock resistance (1000℃ - air cooling): ≥20 times; High-temperature linear shrinkage rate: ≤0.38%, excellent crack resistance.

[0039] Furthermore, the components of the corrosion-resistant heat insulation layer are: Zirconium silicate micro powder accounts for 71%. Aluminum dihydrogen phosphate accounted for 21%. Alumina fiber accounts for 4%. Zirconia fiber accounts for 4%.

[0040] The corrosion-resistant thermal insulation layer formed after curing can meet the following key technical requirements in terms of compressive strength, flexural strength, thermal conductivity, and thermal shock resistance at room temperature and high temperature: Bulk density = 2.28 g / cm³ 3 ; Compressive strength: 110℃×24h=68MPa, 1250℃×3h=75MPa; Flexural strength: 110℃×24h=9.9MPa; 1250℃×3h=11.7MPa; Thermal conductivity of the hot surface at 1000℃ = 0.79 W / (mk); Thermal shock resistance (1000℃ - air cooling) = 12 times.

[0041] Furthermore, the components of the infrared radiation coating are: Aluminum dihydrogen phosphate accounted for 26%. Manganese dioxide accounts for 30%. Ferric oxide accounts for 20%. Copper oxide accounts for 6%. Chromium trioxide accounts for 5% Nickel oxide accounts for 4%. Titanium dioxide accounts for 4%. Cerium oxide accounts for 3%.

[0042] This formulation ensures that the coating has an emissivity of 0.95 in the 2.5–15 μm band, while aluminum dihydrogen phosphate provides strong adhesion. The base material and auxiliary materials work together to achieve high emissivity and thermal shock resistance. Example 3

[0043] The difference between this embodiment and the above embodiment is that the thickness of the infrared radiation coating 3 is 0.8 mm; the thickness of the low thermal conductivity insulation layer 4 is 28 mm; and the thickness of the corrosion-resistant insulation layer 5 is 2 mm.

[0044] The composition of the low thermal conductivity insulation layer is: Polypropylene fiber accounts for 1%. Hollow alumina spheres accounted for 36%. Lightweight mullite accounts for 20%. The proportion of silicon micropowder is 9%. The proportion of alumina micro powder is 5%. Kyanite powder accounts for 5%. Ceramic fiber accounts for 9%, Cement accounted for 11%.

[0045] The performance parameters of the low thermal conductivity insulation layer of this component are as follows: Bulk density: 1.15~1.2 g / cm³ 3 ; Thermal conductivity of the hot surface at 1000℃: 0.24 W / (m·K) Compressive strength after drying at 110℃: 12.5MPa; Compressive strength after calcination at 1250℃: 14.0 MPa; Thermal shock resistance (1000℃ - air cooling): ≥21 times; High-temperature linear shrinkage rate: ≤0.40%, excellent crack resistance.

[0046] Furthermore, the components of the corrosion-resistant heat insulation layer are: Zirconium silicate micro powder accounts for 72%. Aluminum dihydrogen phosphate accounts for 20%. Alumina fiber accounts for 5%. Zirconia fiber accounts for 3%.

[0047] The corrosion-resistant thermal insulation layer formed after curing can meet the following key technical requirements in terms of compressive strength, flexural strength, thermal conductivity, and thermal shock resistance at room temperature and high temperature: Bulk density = 2.28 g / cm³ 3 ; The compressive strength is 67.9 MPa at 110℃ for 24 hours and 76 MPa at 1250℃ for 3 hours. Flexural strength: 110℃×24h=9.9MPa; 1250℃×3h=12MPa; Thermal conductivity of the hot surface at 1000℃ = 0.78 W / (mk); Thermal shock resistance (1000℃ - air cooling) = 10 times.

[0048] Furthermore, the components of the infrared radiation coating are: Aluminum dihydrogen phosphate accounts for 30%. Manganese dioxide accounts for 25%. Ferric oxide accounted for 21%. Copper oxide accounts for 5%. Chromium trioxide accounts for 4% Nickel oxide accounts for 3%. Titanium dioxide accounts for 5%. Cerium oxide accounts for 3%.

[0049] This formulation ensures that the coating has an emissivity of 0.91 in the 2.5–15 μm band, while aluminum dihydrogen phosphate provides strong adhesion. The base material and auxiliary materials work together to achieve high emissivity and thermal shock resistance. Example 4

[0050] The difference between this embodiment and the above embodiment is that the thickness of the infrared radiation coating 3 is 1.5 mm; the thickness of the low thermal conductivity insulation layer 4 is 30 mm; and the thickness of the corrosion-resistant insulation layer 5 is 1 mm.

[0051] The composition of the low thermal conductivity insulation layer is: Polypropylene fiber accounts for 1.2%. Hollow alumina spheres accounted for 37%. Lightweight mullite accounts for 17%. The proportion of silicon micropowder is 11%. The alumina micro powder accounts for 8%. Kyanite powder accounts for 3%. Ceramic fiber accounts for 12%. Cement accounts for 8%.

[0052] The performance parameters of the low thermal conductivity insulation layer of this component are as follows: Bulk density: 1.12~1.17 g / cm³ 3 ; Thermal conductivity of the hot surface at 1000℃: 0.24 W / (m·K) Compressive strength after drying at 110℃: 13.0 MPa; Compressive strength after calcination at 1250℃: 14.5MPa; Thermal shock resistance (1000℃ - air cooling): ≥24 cycles; High-temperature linear shrinkage rate: ≤0.35%, stable microporous structure, and outstanding heat insulation effect.

[0053] Furthermore, the components of the corrosion-resistant heat insulation layer are: Zirconium silicate micro powder accounts for 70%. Aluminum dihydrogen phosphate accounts for 25%. Alumina fiber accounts for 3%. Zirconia fiber accounts for 2%.

[0054] The corrosion-resistant thermal insulation layer formed after curing can meet the following key technical requirements in terms of compressive strength, flexural strength, thermal conductivity, and thermal shock resistance at room temperature and high temperature: Bulk density = 2.25 g / cm³ 3 ; The compressive strength is 67.7 MPa at 110℃ for 24 hours and 73.8 MPa at 1250℃ for 3 hours. Flexural strength: 10.5 MPa at 110℃ for 24 hours; 1250℃ for 3 hours; Thermal conductivity of the hot surface at 1000℃ = 0.77 W / (mk); Thermal shock resistance (1000℃ - air cooling) = 14 times.

[0055] Furthermore, the components of the infrared radiation coating are: Aluminum dihydrogen phosphate accounts for 27%. Manganese dioxide accounted for 27%. Ferric oxide accounts for 25%. Copper oxide accounts for 5%. Chromium trioxide accounts for 4% Nickel oxide accounts for 5%. Titanium dioxide accounts for 3%. Cerium oxide accounts for 2%.

[0056] This formulation ensures that the coating has an emissivity of 0.93 in the 2.5–15 μm band, while aluminum dihydrogen phosphate provides strong adhesion. The base material and auxiliary materials work together to achieve high emissivity and thermal shock resistance. Example 5

[0057] The difference between this embodiment and the above embodiment is that the thickness of the infrared radiation coating 3 is 1 mm; the thickness of the low thermal conductivity insulation layer 4 is 20 mm; and the thickness of the corrosion-resistant insulation layer 5 is 1.2 mm.

[0058] The composition of the low thermal conductivity insulation layer is: Polypropylene fiber accounts for 0.8%. Hollow alumina spheres accounted for 38%. Lightweight mullite accounts for 15%. The silicon micropowder accounts for 12%. The alumina micro powder accounts for 6.5%. Kyanite powder accounts for 3%. Ceramic fiber accounts for 8%. Cement accounts for 10.5%.

[0059] The performance parameters of the low thermal conductivity insulation layer of this component are as follows: Bulk density: 1.16~1.21 g / cm3; Thermal conductivity of the hot surface at 1000℃: 0.27 W / (m·K) Compressive strength after drying at 110℃: 12.3 MPa; Compressive strength after calcination at 1250℃: 13.9 MPa; Thermal shock resistance (1000℃ - air cooling): ≥21 times; High-temperature linear shrinkage rate: ≤0.42%, with good high-temperature volume compensation effect.

[0060] Furthermore, the components of the corrosion-resistant heat insulation layer are: Zirconium silicate micro powder accounts for 75%. Aluminum dihydrogen phosphate accounts for 20%. Alumina fiber accounts for 3%. Zirconia fiber accounts for 2%.

[0061] The corrosion-resistant thermal insulation layer formed after curing can meet the following key technical requirements in terms of compressive strength, flexural strength, thermal conductivity, and thermal shock resistance at room temperature and high temperature: Bulk density ≤2.28g / cm³ 3 ; The compressive strength is 68 MPa at 110℃ for 24 hours and 74.2 MPa at 1250℃ for 3 hours. Flexural strength: 110℃×24h=9.9MPa; 1250℃×3h=11.7MPa; Thermal conductivity of the hot surface at 1000℃ = 0.79 W / (mk); Thermal shock resistance (1000℃ - air cooling) = 14 times.

[0062] Furthermore, the components of the infrared radiation coating are: Aluminum dihydrogen phosphate accounted for 28%. Manganese dioxide accounted for 26%. Ferric oxide accounted for 22%. Copper oxide accounts for 8%. Chromium trioxide accounts for 6% Nickel oxide accounts for 3%. Titanium dioxide accounts for 3%. Cerium oxide accounts for 2%.

[0063] This formulation ensures an emissivity of 0.91 in the 2.5–15 μm band, while aluminum dihydrogen phosphate provides strong adhesion. The base material and additives work together to achieve high emissivity and thermal shock resistance.

[0064] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A ceramic-based gradient composite thermal insulation expansion joint device for high-temperature pipelines, characterized in that, The tube includes a body and an inner lining (2). The inner lining (2) is disposed inside the tube body (1). The inner lining (2) includes an infrared radiation coating (3), a low thermal conductivity insulation layer (4), and a corrosion-resistant insulation layer (5). The infrared radiation coating (3), the low thermal conductivity insulation layer (4), and the corrosion-resistant insulation layer (5) are arranged sequentially from the inside to the outside. The low thermal conductivity insulation layer (4) is made by casting, curing, and flame baking of raw materials containing the following components by mass percentage: The proportion of polypropylene fiber is 0.5%-1.5%. Hollow alumina spheres account for 35%-40%. The proportion of lightweight mullite is 15%-20%. The proportion of silicon micropowder is 8%-12%. The proportion of alumina micro powder is 5%-8%. The proportion of kyanite powder is 3%-5%. The proportion of ceramic fiber is 8%-12%. Cement accounts for 8%-12%.

2. The ceramic-based gradient composite thermal insulation expansion joint device for high-temperature pipelines as described in claim 1, characterized in that, The corrosion-resistant heat insulation layer (5) is formed by ball milling and mixing raw materials containing the following mass percentage components, spraying with deionized water, and fast drying and curing with an oxy-acetylene flame: The proportion of zirconium silicate micro powder is 70%-75%. Aluminum dihydrogen phosphate accounts for 20%-25%. The proportion of alumina fiber is 3%-5%. Zirconia fiber accounts for 2%-4%.

3. The ceramic-based gradient composite thermal insulation expansion joint device for high-temperature pipelines as described in claim 2, characterized in that, The infrared radiation coating (3) is formed by ball milling, spraying, and curing a coating containing the following components by mass percentage: Aluminum dihydrogen phosphate accounts for 25%-30%. The proportion of manganese dioxide is 25%-30%. The content of ferric oxide is 20%-25%. The proportion of copper oxide is 5%-8%. Chromium trioxide accounts for 4%-6% of the total content. Nickel oxide accounts for 3%-5%, The titanium dioxide content is 3%-5%. Cerium oxide accounts for 2%-4%.

4. The ceramic-based gradient composite thermal insulation expansion joint device for high-temperature pipelines as described in claim 3, characterized in that, The body includes an end tube (11), a corrugated pipe (8), and a connector (9). There are two end tubes (11). The corrugated pipe (8) is located between the two end tubes (11). The two ends of the corrugated pipe (8) are welded to the end tube (11). The connector (9) passes over the corrugated pipe (8) and is connected to the end tube (11). The liner (2) is located in the channel of the tube body (1).

5. The ceramic-based gradient composite thermal insulation expansion joint device for high-temperature pipelines as described in claim 4, characterized in that, The infrared radiation coating 3 has a thickness of 0.8-1.5 mm; the low thermal conductivity insulation layer 4 has a thickness of 10-30 mm; and the corrosion-resistant insulation layer 5 has a thickness of 1-2 mm.

6. The ceramic-based gradient composite thermal insulation expansion joint device for high-temperature pipelines as described in claim 5, characterized in that, It is also provided with an outer liner (6), which is located outside the end pipe (11) and the corrugated pipe (8). The outer liner (6) and the inner liner (2) are arranged symmetrically in terms of layer structure.

7. The ceramic-based expansion joint for high-temperature pipelines as described in claim 6, characterized in that, The connector (9) includes several sets of components. Each set of components includes a connecting screw (91), a nut (92) and a connecting plate (93). There are two connecting plates (93). The two connecting plates (93) are respectively fixed to the end tube (11). One end of the connecting plate (93) is connected to the end tube (11), and the other end is provided with a through hole. The connecting screw passes through the through hole and is fixed by the nut (92).

8. The ceramic-based expansion joint for high-temperature pipelines as described in claim 7, characterized in that, The outer liner (6) is also provided with an outer protective cover (7) and an anchor (10). The anchor (10) is fixed to the side wall of the end tube (11). The anchor (10) is Y-shaped and extends into the low thermal conductivity insulation layer (4).